Enhanced Hole Extraction in Perovskite Solar Cells Through Carbon Nanotubes - Habisreutinger, SN; Leijtens, T; Eperon, G; Stranks, S; Nicholas, R; Snaith, H (American Chemical Society, 2014)
Here, we report the use of polymer-wrapped carbon nanotubes as a means to enhance charge extraction through undoped spiro-OMeTAD. With this approach a good solar cell performance is achieved without the implementation of conventional doping methods. We demonstrate that a stratified two-layer architecture of sequentially deposited layers of carbon nanotubes and spiro-OMeTAD, outperforms a conventional blend of the hole-conductor and the carbon nanotubes. We also provide insights into the mechanism of the rapid hole extraction observed in the two-layer approach.